Antibacterial activity of hexane and ethanolic extracts of marine macroalgae of the Bay of Ancón, Lima – Peru - Muñoz A., Ramón (2020)
The antimicrobial activities of ethanolic and hexane extracts of nine species of marine macroalgae collected in the intertidal zone of the San Francisco beach, Ancón, in Lima, Peru were evaluated. It was performed in vitro against a panel of standard Gram-positive bacteria (Staphylococcus aureus ATCC 6538, Bacillus subtilis ATCC 6633 and Enterococcus faecalis ATCC 51922) and Gram-negative (Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 9027 and Salmonella Typhimurium 14028). The ethanolic extracts were of higher yield (67%) compared to hexanes (33%), especially against the Gram-positive, being the extract obtained from Ulva enteromorpha var. intestinalis and U. nematoidea the most efficient against S. aureus ATCC 6538 (74.1 and 78.2% inhibition, respectively). The ethanol extracts of Cladophora sp and U. nematoidea against B. subtilis ATCC 6633 showed moderate to low inhibitions (52.5 and 33%, respectively). The ethanolic extracts of U. enteromorpha and Cladophora sp against S. Typhimurium showed only 40% inhibition. The ethanol extract of Cladophora sp was the only one that presented antimicrobial activity against the five bacterial strains and therefore it was chosen to determine the Minimum Inhibitory Concentration (MIC), which resulted in 12.5 and 25 mg/ml against B. subtilis ATCC 6633 and S aureus ATCC 6538, respectively. It is concluded that most of the macroalgae studied contain inhibitory compounds, whose ethanolic and hexane extracts are capable of inhibiting the growth of pathogenic bacteria.